Expedient Choice of Transforms in Phase-Diagramming - Conlisk, J.; Ramanathan, R. (Review of Economic Studies, 1970)
J. Conlisk, R. Ramanathan; Expedient Choice of Transforms in Phase-Diagramming1, The Review of Economic Studies, Volume 37, Issue 3, 1 July 1970, Pages 441